Effectiveness of Using LKPD Based on Realistic Mathematic Education (RME) to Improve the Mathematical Communication Skills of High School Students - Setiawati, Reza; ., Pixyoriza (JURNAL PENDIDIKAN, 2024)
This research aims to determine the effectiveness of using LKPD based on Realistic Mathematic Education in improving the communication skills of class X students at SMA Negeri 2 Natar for the 2022/2023 academic year. This quantitative research uses the Quasi-Experimental Design method and Pretest-Posttest Control Group Design. Data collection techniques in this research include interviews, observation, and tests of mathematical communication skills. The analysis techniques used are descriptive statistics and t-tests. Based on the results of the t-test on increasing mathematical communication skills, 0.00 < 0.005, and with an N-gain of 0.69, it meets the quite effective category. So it can be concluded that LKPD based on Realistic Mathematic Education is effective in improving mathematical communication skills to make students more active during learning using LKPD based on Realistic Mathematic Education on functional material in class X MIPA.